2020
DOI: 10.1111/idj.12574
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of dental aesthetics on dental patients

Abstract: Objective: This study aimed to evaluate the contribution of demographic and clinical characteristics on the psychosocial impact of dental aesthetics of dental patients. Methods: The psychosocial impact of dental aesthetics was assessed by the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ). Data validity was estimated using confirmatory factor analysis (CFA). Reliability was assessed using standardised Cronbach's alpha coefficient (a). A structural model was developed to assess the contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
4
11
0
7
Order By: Relevance
“…Regarding the PIDAQ-Fi, the results that fit the factorial model to the data confirm the four-factor structure of PIDAQ, corroborating the findings when PIDAQ is applied to other samples and contexts [11,[24][25][26]. In addition, a high correlation was observed in the present study between three factors of PIDAQ, which compromised the discriminant validity and, considering the theory of the instrument, provides support for the elaboration of a second-order hierarchical model (SOHM).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Regarding the PIDAQ-Fi, the results that fit the factorial model to the data confirm the four-factor structure of PIDAQ, corroborating the findings when PIDAQ is applied to other samples and contexts [11,[24][25][26]. In addition, a high correlation was observed in the present study between three factors of PIDAQ, which compromised the discriminant validity and, considering the theory of the instrument, provides support for the elaboration of a second-order hierarchical model (SOHM).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, a high correlation was observed in the present study between three factors of PIDAQ, which compromised the discriminant validity and, considering the theory of the instrument, provides support for the elaboration of a second-order hierarchical model (SOHM). The SOHM showed an adequate fit to the data, as has already been observed in a Brazilian sample [26]. These authors suggested that, after confirming the SOHM, it is possible to obtain a general score for the psychosocial impact of dental aesthetics, in addition to the scores for each first factor.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations